Regulatory Technology (RegTech): The Solution to Prevent Money Laundering in Indonesia - Alivia Meyrizka Utami; Mega Dwi Septivani (Telaah Bisnis, 2022)
Since the 2008 financial crisis, the complexity of regulations and the use of technology and innovation in the financial sector have increased. This makes banks as financial institutions starting to adapt to financial technology very vulnerable to technological risks, one of which is money laundering. Regulatory Technology (RegTech) is a technology trend to assist bank management in supporting regulatory compliance efforts and offering money laundering prevention solutions. Based on this, this study aims to examine the relationship of RegTech, which is represented by three independent variables: Electronic Know Your Customer (e-KYC), Transaction Monitoring, and Time and Cost Efficiency, on Money Laundering Prevention. This study shows that transaction monitoring, as well as cost and time efficiency, have a significant effect on money laundering prevention. In contrast, e-KYC does not affect money laundering prevention. This research is intended to provide valuable insights to Financial Institutions to increase awareness of the importance of adopting new technologies and maintaining good relations with regulators to prevent money laundering in Indonesia.